Ozonetherapy for the treatment of endometritis (Ozone Therapy Global Journal, 2014)
The inflammatory diseases of female genital organs are numbered among the mostfrequent pathologies of fertile women. In order to increase the efficiency of treatmentand to avoid possible side effects we have used intrauterine irrigations with ozonizeddist i l led water in case of acut e endomet ritis. This method of t reat me nt has b eenprovided to 60 patients wi th postnata l and postabortive endometritis. Based on thereceived results, we have dr aw n a c onc lusion that in t he course of treatment allpatients showed an impr ovement in general s tate, bod y tempe rature re turn ed tonor ma l, sympto ms o f in toxication decreased, slee p and appetite got better, painsyndrom disappeared faster, pathological discharges were eliminated. The results oflaboratory investigations have demonstrated a credible decrease in ESR, normalizationof leukoc yte number, a de crease in circulating immune complexes .Thus, for treatment of endometritis we may recommend the given method o fozone ther apy to be used in combination with a basi c a nti-inflammatory therapy.